Peran Dukungan Sosial dalam Meningkatkan Minat Belajar Peserta Didik: Kajian Literatur: The Role of Social Support in Enhancing Students’ Learning Interest: A Literature Review - Mardatillah, Mardatillah; Siska Putri Ayu (Litera Academica Publishing, 2025)
Learning interest is a crucial internal factor that influences students’ academic engagement and overall educational outcomes. Various studies consistently highlight social support—originating from parents, peers, teachers, and the learning environment—as a significant external determinant that strengthens students’ motivation and willingness to learn. This literature review aims to synthesize empirical findings from quantitative and qualitative research conducted in diverse educational settings to examine how different forms of social support contribute to the enhancement of learning interest. Results of the reviewed studies show that parental support fosters emotional security and learning discipline, peer support promotes academic encouragement and social belonging, and teacher support strengthens students’ confidence and self-regulated learning. Additionally, supportive learning environments and adequate learning facilities further reinforce students' motivation. Overall, the findings indicate that social support plays a fundamental and multidimensional role in shaping learning interest, suggesting the need for collaborative involvement among families, schools, and peer groups to optimize students’ academic development.